2014
DOI: 10.4992/jjpsy.85.69
|View full text |Cite
|
Sign up to set email alerts
|

The Hedonic and Eudaimonic Motives for Activities (HEMA) in Japan: The pursuit of well-being

Abstract: Hedonia (seeking pleasure and relaxation) and eudaimonia (seeking to improve oneself in congruence with one's values) uniquely contribute to well-being. The authors developed and tested the construct validity of a Japanese version of the Hedonic and Eudaimonic Motives for Activities (HEMA) scale that had been originally developed in North America. Drawing on the theoretical and empirical evidence from research on emotion, we proposed that people would pursue well-being in three different directions: pleasure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 22 publications
3
27
0
Order By: Relevance
“…Based on the theoretical assumptions underlying the HEMA scale, a model separating the hedonic and the eudaimonic factor was expected. Previous exploratory analyses revealed the existence of such two-factor structure (Huta and Ryan, 2010; Anić, 2014). However, a recent confirmatory analysis of the Japanese version of the HEMA scale revealed that a three-factor structure is a better representation of the scale's structure (Asano et al, 2014).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Based on the theoretical assumptions underlying the HEMA scale, a model separating the hedonic and the eudaimonic factor was expected. Previous exploratory analyses revealed the existence of such two-factor structure (Huta and Ryan, 2010; Anić, 2014). However, a recent confirmatory analysis of the Japanese version of the HEMA scale revealed that a three-factor structure is a better representation of the scale's structure (Asano et al, 2014).…”
Section: Resultsmentioning
confidence: 97%
“…Previous exploratory analyses revealed the existence of such two-factor structure (Huta and Ryan, 2010; Anić, 2014). However, a recent confirmatory analysis of the Japanese version of the HEMA scale revealed that a three-factor structure is a better representation of the scale's structure (Asano et al, 2014). Therefore, our goals were to (1) determine the factor structure of the scale, and (2) validate the performance of the short 8-item instrument.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The HEMA scale has been translated into many languages, including German, Swedish, Polish, Italian, and Japanese (see, for a review, Huta, 2016). Although the HEMA scale was originally developed to operationalize hedonic and eudaimonic orientations (Huta and Ryan, 2010), recent evidence has shown that the hedonic orientation of the scale can be divided into two different components (Asano et al, 2014(Asano et al, , 2018Bujacz et al, 2014;Braaten et al, 2019). "Hedonic pleasure" and "hedonic relaxation" orientations refer to striving to feel enjoyment and comfort, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…"Eudaimonic" orientation refers to striving to do what is meaningful, even if difficult to achieve. Research on the Japanese HEMA scale with student samples demonstrated that the three-factor model was better than the two-factor model and showed that the three subscales were adequately reliable and valid (Asano et al, 2014(Asano et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%